Use of Electronic Health Records for Early Detection of High-Cost, Low Back Pain Patients - Daniel D Maeng; Walter F Stewart; Xiaowei Yan; Joseph A Boscarino; Jack Mardekian; James Harnett; Michael R Von Korff (Pain Research and Management)
BACKGROUND: Low back pain (LBP) is a debilitating condition that is complex to manage. One reason is that clinicians lack means to identify early on patients who are likely to become high care utilizers.